Exploring the efficacy of laser speckle contrast imaging in the stratified diagnosis of rosacea: a quantitative analysis of facial blood flow dynamics across varied regions - Liao, Jin-Feng; Jiang, Xue-Mei; Xie, Zhen; Lei, Hua; Luo, Juan; Lv, Yu; Liu, Gang; Mao, Yujie; Song, Si-Yuan; Wang, Yi (Frontiers in Immunology, 2024)
Background Rosacea has a high incidence, significantly impacts quality of life, and lacks sufficient diagnostic techniques. This study aimed to investigate the feasibility of laser speckle contrast imaging (LSCI) for measuring facial blood perfusion in patients with rosacea and to identify differences in blood flow among various facial regions associated with different rosacea subtypes. Methods From June to December 2023, 45 patients were recruited, with 9 excluded, leaving 36 subjects: 12 with erythematotelangiectatic rosacea (ETR), 12 with papulopustular rosacea (PPR), and 12 healthy controls. The Think View multispectral imaging analyzer assessed inflammation via gray reading values across the full face and five facial areas: forehead, nose, cheeks, and chin. LSCI measured and analyzed blood perfusion in the same areas. Plasma biomarkers interleukin-6 (IL-6), IL-1β, and tumor necrosis factor-α (TNF-α) were tested in different groups. Results Both ETR and PPR groups showed increased average blood perfusion and facial inflammation intensity by gray values compared to controls, with statistically significant differences. Average blood perfusion of ETR and PPR groups showed increased values in the forehead, cheeks, and nose, compared to controls, and the values in the cheeks were statistically different between ETR and PPR. The facial inflammation intensity of the ETR group showed increased values in the forehead and cheeks, and the PPR group showed increased gray values in the forehead, cheeks, nose, and chin compared to controls, and the values for the cheeks, nose, and chin were statistically significantly different between ETR and PPR. Plasma biomarkers IL-6, IL-1β, and TNF-α were significantly elevated in both ETR and PPR groups compared to controls. Conclusion LSCI is a valuable, non-invasive tool for assessing blood flow dynamics in rosacea, providing a data foundation for clinical research. Different rosacea subtypes exhibit distinct lesion distribution and blood flow patterns, and both ETR and PPR could affect all facial areas, particularly the cheeks in ETR and the forehead, nose, and chin in PPR.